Proteinase 3 (PR3)-Antineutrophil Cytoplasmic Antibody in a Patient with Minimal Change Disease: An Unusual Finding - Joana Freitas; Inês Sala; João Oliveira; Andreia Campos; Sofia Santos; Josefina Santos; António Cabrita (Publicações Ciência e Vida, 2022)
Antineutrophil cytoplasmic antibodies (ANCA) are useful as markers for systemic vasculitis. PR3-ANCA antibodies have been also identified in association with chronic inflammatory and infectious conditions, other autoimmune diseases, malignancy, and certain drugs. The association of PR3 and minimal change disease (MCD) without vasculitis is not an expected finding. We report a case of MCD with PR3-ANCA positive title and no histopathological findings of vasculitis. This reports to an 86-year-old Caucasian woman without relevant past medical history and a normal renal function one month before presentation with sudden-onset nephrotic syndrome and rapidly progressive renal failure. Renal ultrasound was normal. Autoimmune screening using enzyme-linked immunosorbent assay (ELISA) revealed PR3-ANCA high titers (238.7UQ). Renal biopsy did not show vasculitis or crescentic glomerulonephritis. The glomeruli were normal. Autoimmune, inflammatory, infectious and malignant diseases were excluded. MCD was assumed and she started prednisolone with clinical and analytical improvement. ANCA-associated glomerular disease can coexist with a variety of other glomerular diseases including membranous nephropathy, lupus nephritis, IgA nephropathy, and bacterial infection-related glomerulonephritis. This association could be an incidental finding, but there may be an association with MCD not previously reported. Our case emphasizes the importance of performing renal biopsies before embarking on a full-scale immunosuppression therapy based on ANCA title alone.